Implementasi Program Pengembangan Anak Usia Dini Holistik Integratif Di Tk Al Wildan Cibodas Garut - Kartika, Windari; Chalid, Choiriyah; Hamidah, Agustin (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Teacher Strategy in Improving Integrative Holistic Education in Early Age Children 4-5 Years at Al Wildan Kindergarten Cibodas Garut, Thesis, Jakarta: Panca Sakti University Bekasi Educational Sciences 2024.This research aims to identify teacher strategies in improving integrative holistic education for early childhood 4-5 years at Al Wildan Cibodas Kindergarten. Specifically, you must know the concept of integrative holistic education, know integrative holistic learning strategies, and know the stages of integrative holistic learning. The research method used is a qualitative descriptive method. According to Sugiono (2018:213), qualitative research methods are research methods that are based on philosophy and are used to study scientific (experimental) conditions where the researcher as the instrument and technique collects and analyzes qualitative data with greater emphasis on meaning. According to Moleong (2017:6), qualitative research refers to a comprehensive understanding of phenomena such as behavior, cognition, motivation and behavior experienced by research subjects through words and verbal explanations. Language depends on a particular context. The research results showed that the results of interviews with teachers and students at Al Wildan Kindergarten showed that 40% understood integrative holistic education and 60% did not understand integrative holistic education. After further research, the cause of the lack of understanding about integrative holistic education is due to a lack of socialization about integrative holistic education, and teacher capacity in integrative holistic education is still limited, causing teachers and parents to not clearly understand the importance of integrated integrative holistic education. and lack of parental involvement in preschool education. The results of this research are very important in improving the growth and development of early childhood. Because by understanding the meaning of holistic, integrative education, every aspect of early childhood development can be achieved optimally